(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2016)
Objective: The objective of the study was to measure the proportion of GDM in antenatal outdoor of a hospital, to find out the mean gestational period at which most delivery occurred in GDM and to assess the perinatal outcome. Study design : It was a prospective analytical study conducted in BSMMU, from March,2010 to February,2011. Method: 1489 pregnant women, not known to be diabetic previously, were selected by consecutive sampling in first trimester from Obstetrics outdoor, BSMMU. Their FBS and blood glucose 2hrs after 75gm oral glucose were recorded. We investigated blood glucose in first, second and third trimester in the same pregnant women for screening GDM. Cut off GDM values in fasting stage was e 6.1mmol/l and 2 hrs after 75gm oral glucose was e 7.8mmol/l . Result: The proportion of GDM in Obstetrics Outdoor of BSMMU was 6.85%. The mean gestational period at which delivery occurred was lower in GDM ( 36.9 ± 2.2 wks ) than that in non-GDM (39 ± 1.6 wks ) .The most common (31.4%) gestational week during delivery in GDM was 37 completed weeks. Birth weight of 40.2% babies were in the range of 2.5kg to 3.0kg, 31.4% in the range of 3.1 to 3.5 kg and 1% neonate died after birth in GDM. Conclusion: Presently GDM is diagnosed early. The mean gestational period at delivery in GDM is 36.9±2.2 wks. Majority neonatal birth weight is of normal range. Neonatal mortality rate is not increased and is not significantly different from non-GDM women. J Bangladesh Coll Phys Surg 2015; 33(2): 79-85